Smart grid security : Second International Workshop, SmartGridSec 2014, Munich, Germany, February 26, 2014, Revised Selected Papers - Cuellar, Jorge (Lecture Notes in Computer Science, 2014)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International Workshop on Smart Grid Security, SmartGridSec 2014, held in Munich, Germany, in February 2014. The volume contains twelve corrected and extended papers presented at the workshop which have undergone two rounds of reviewing and improvement. The engineering, deployment and operation of the future Smart Grid will be an enormous project that will require the active participation of many stakeholders with different interests and views regarding the security and privacy goals, technologies, and solutions. There is an increasing need for workshops that bring together researchers from different communities, from academia and industry, to discuss open research topics in the area of future Smart Grid security.